Transpression Regime in the Southern Alps and Possible Extension Regime in Canterbury, New Zealand (The Australasian Institute of Mining and Metallurgy, 1990)
Detailed mapping in the Permian-Triassic clastic sediments of the Southern Alps delineates a number of strike-slip faults, both dextral and sinistral, associated with the major Alpine Fault to the west and displacing a tight array of fault blocks. Concurrent steeply plunging folds are deforming early major folds of probable Cretaceous age, and generating schist locally. To the east a major collapse zone has developed along the crest of a Cretaceous anticline, located over an ancient Permian submarine scarp, with a number of small normal faults. Further east, extensive Carboniferous to Triassic rocks of much the same appearance are exposed as horsts and grabens in a large possible extension zone through central and east Canterbury. This may have crept incrementally from Cretaceous from the offshore Bounty Trough to reach the eastern margins of the Southern Alps in the Pleistocene.